2012
DOI: 10.2527/jas.2011-5022
|View full text |Cite
|
Sign up to set email alerts
|

Application of a computer vision system to classify beef as normal or dark, firm, and dry1

Abstract: The purpose of this research was to evaluate the possibility of using computer vision systems (CVS) to detect DFD beef. The experimental material consisted of beef obtained from 60 carcasses (M. semimembranosus) that were 48 h postmortem. The beef was classified into 2 quality groups according to pH: normal (pH < 5.8) or DFD (pH ≥ 5.8). L*, a*, and b* color components were determined in the experimental materials using both CIELab and a CVS using 3 color models: RGB (red, green, blue), HSV (hue, saturation, va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
3
12
0
3
Order By: Relevance
“…Results for a* (redness) and b* (yellowness) from animals untreated with vitamin D 3 correspond to those obtained by other authors for beef meat quality without defects (normal meat) (19,20). Values of a* achieved by Hope-Jones et al (2) were considerably lower for a dose of 7.0 × 10 6 IU of vitamin D 3 administered 3 days before slaughter than our data collected under the same supplementation parameters (vitamin D 3 dose and supplementation time).…”
Section: Discussionsupporting
confidence: 88%
“…Results for a* (redness) and b* (yellowness) from animals untreated with vitamin D 3 correspond to those obtained by other authors for beef meat quality without defects (normal meat) (19,20). Values of a* achieved by Hope-Jones et al (2) were considerably lower for a dose of 7.0 × 10 6 IU of vitamin D 3 administered 3 days before slaughter than our data collected under the same supplementation parameters (vitamin D 3 dose and supplementation time).…”
Section: Discussionsupporting
confidence: 88%
“…The least MMb formed in MRA analysis in high pHu group is in concordance with other findings in this study, such as higher redness (more a* and a*/b*) and lower discoloration throughout storage (less Hue and surface MMb), It demonstrates the oxidative protection of high pHu regarding red color stability, as authors have been documented (ABRIL et al, 2001;CHMIEL et al, 2012;ENGLISH et al, 2016;GEORGE;STRATMANN, 1952;MCKEITH et al, 2016;STACKHOUSE et al, 2016;WULF;WISE, 1999 The greater content of NADH in the high pHu group could also be a factor for the increased MRA this group had in this study.…”
Section: Surface Pigmentssupporting
confidence: 92%
“…Image capturing was performed according to method developed by Chmiel et al (2011) and Chmiel et al (2012). The prepared pictures were analyzed using IMAGE ANALYZER (software developed for Division of Meat Technology at Warsaw University of Life Sciences e SGGW).…”
Section: Image Analysismentioning
confidence: 99%
“…In the study of Chmiel, Słowi nski, and Dasiewicz (2011) it was proven that CVS can be used to detect PSE defect in m. longissimus lumborum. While detecting the DFD (dark, firm, dry) in beef meat obtained from m. semimembranosus it was found that the CVS method had 90% detection efficiency (Chmiel, Słowi nski, Dasiewicz, & Florowski, 2012).…”
Section: Introductionmentioning
confidence: 99%